2018
DOI: 10.1128/aac.00465-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Retinoic Acid Receptor Agonists as Potent Hepatitis B Virus Inhibitors via a Drug Repurposing Screen

Abstract: Currently available therapies for chronic hepatitis B virus (HBV) infection can efficiently reduce viremia but induce hepatitis B surface antigen (HBsAg) loss in very few patients; also, these therapies do not greatly affect the viral covalently closed circular DNA (cccDNA). To discover new agents with complementary anti-HBV effects, we performed a drug repurposing screen of 1,018 Food and Drug Administration (FDA)-approved compounds using HBV-infected primary human hepatocytes (PHH). Several compounds belongi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…Similarly, Chen et al reported that the antiviral effects of RA against enterovirus 71 are mediated through IFN‐α and RIG‐I 25 . Natural and synthetic retinoids also have direct inhibitory effects on replication of a number of viruses, including hepatitis B virus (HBV), cytomegalovirus, influenza, MeV, and norovirus 27‐30 . There is also evidence that activation of retinoid signalling can potently inhibit coronaviruses 31 .…”
Section: Retinoids As Immunomodulators and Potential Adjuvants With Imentioning
confidence: 97%
“…Similarly, Chen et al reported that the antiviral effects of RA against enterovirus 71 are mediated through IFN‐α and RIG‐I 25 . Natural and synthetic retinoids also have direct inhibitory effects on replication of a number of viruses, including hepatitis B virus (HBV), cytomegalovirus, influenza, MeV, and norovirus 27‐30 . There is also evidence that activation of retinoid signalling can potently inhibit coronaviruses 31 .…”
Section: Retinoids As Immunomodulators and Potential Adjuvants With Imentioning
confidence: 97%
“…The most potent hit, Tazarotene, inhibits transcription from cccDNA with IC50 value of 20~75 nM without reducing cccDNA levels. It targets mostly RAR but not RAR and RAR in infected primary hepatocytes [108]. Nkongolo et al identified Tamibarotene (Am80) using another FDA approved drug library and further compared Tamibarotene (RAR-specific) with other agonists, Tazarotene (RAR/-specific), Adapalene (RAR-specific), all-trans retinoic acid (pan-activity).…”
Section: Retinoic Acid Receptor Agonistsmentioning
confidence: 99%
“…Some vitamins, like vitamins E, D and A, have been used in clinical trials for the treatment of patients with persistent viral infections, including HBV, HCV and HIV. These micronutrients have been demonstrated to enhance both the innate and the adaptive immunity against these pathogens (61,(68)(69)(70)(71)(72)(73) and to decrease susceptibility of CD4þ T lymphocytes to HIV-1 infection (74) . Furthermore, vitamins A, D and E have been suggested to improve innate and adaptive immune response against respiratory viruses, including influenza virus, rhinovirus and respiratory syncytial virus both in vivo and in vitro studies (75) .…”
Section: Defective and Dysfunctional Immune Response In Patients Withmentioning
confidence: 99%